Evidence-Based Palliative Care: Innovations in Pain Management and Quality of Life Improvement - Daiki Nishida; Miku Fujita; Zulkahfi Zulkahfi; Misroh Mulianingsih (Journal of World Future Medicine, Health and Nursing, 2025)
Palliative care has undergone significant transformation as global health systems respond to increasing rates of chronic and life-limiting illnesses. Persistent challenges in pain management, symptom control, and psychosocial support highlight the need for evidence-based innovations that enhance patient quality of life. This study aims to examine emerging evidence-based approaches in palliative pain management and evaluate their impact on improving holistic well-being for patients receiving palliative care. A systematic review methodology was employed, synthesizing findings from clinical trials, observational studies, and multidisciplinary intervention reports published over the past decade. The results indicate that multimodal pain management strategies combining pharmacological optimization, non-pharmacological therapies, and digital monitoring technologies significantly reduce pain severity and enhance patient comfort. The evidence further demonstrates that integrative interventions, such as mindfulness-based therapies, personalized care planning, and family-centered support models, contribute meaningfully to psychological resilience and perceived quality of life. The study concludes that evidence-based innovations in palliative care provide measurable benefits across physical, emotional, and social dimensions, underscoring the importance of adopting interdisciplinary and patient-centered approaches.